Shifting from the Status Quo: A Conceptual Framework to Enhance the Field of Sport for Development Integrating the Capabilities Approach and Critical Pedagogy - Sandeep Dutta; Justin Evanovich; Max Klein (Youth)
Scholars have called for a better understanding of how sport might contribute to development efforts. Theoretical efforts that can support a critical examination of Sport for Development (SfD) practice have been scarce. In this article, the authors propose a new framework integrating the capabilities approach with critical pedagogy. The authors argue that the capabilities approach provides a framework for how people can be provided experiences through SfD activities. Integrating the principles of critical pedagogy supports SfD programs in celebrating local community strengths and incorporating existing assets into program design and delivery. The authors also provide a diagrammatic model that can support future inquiry into research and practice within SfD.